Halictoxenos xenomorphae sp. nov.: a new record genus and a new species from China with observed biology (Strepsiptera: Stylopidae) - Zheng, Xuhongyi; Gong, Dewen; Li, Jianbo; Zhou, Changfa (Zootaxa, 2025)
Halictoxenos is a widely distributed genus of Strepsiptera that parasitizes bees of the family Halictidae, comprising approximately 23 species across Asia, Europe, Africa, and America. Previous records from Asia were limited to nine species reported exclusively from two island nations: Japan (Palearctic region) and the Philippines (Oriental region). This study documents the discovery of a new species in eastern China, along with significant biological observations from field studies. Notably, all 16 specimens observed over three years of monitoring were female, suggesting extreme male scarcity and potential parthenogenesis in this species. This discovery represents not only a new record genus from China with mysterious life history, but also provide some new clues for the biology and biogeography of this group.